From baby brain to mommy brain: Widespread gray matter gain after giving birth. (May 2020) - Luders, Eileen; Kurth, Florian; Gingnell, Malin; Engman, Jonas; Yong, Eu-Leong; Poromaa, Inger S.; Gaser, Christian
Abstract: Pregnancy results in obvious physiological changes to the female body, but data as to what happens to the maternal brain after giving birth are sparse as well as inconsistent. The overall goal of this study is to determine the nature of cerebral change in the postpartum period. For this purpose, we analyzed T1-weighted brain images of 14 healthy women (age range: 25–38 years) at two time points, specifically within 1–2 days of childbirth (immediate postpartum) and at 4–6 weeks after childbirth (late postpartum). When comparing voxel-wise gray matter between these two time points, there was no evidence of any significant decrease . Instead, we detected a pronounced gray matter increase involving both cortical and subcortical regions, such as the pre- and postcentral gyrus, the frontal and central operculum, the inferior frontal gyrus, the precuneus, and the middle occipital gyrus, as well as the thalamus and caudate. These structural changes occurring within only 4–6 weeks after delivery are reflective of a high degree of neuroplasticity and massive adaptations in the maternal brain. They may suggest a restoration of brain tissue following pregnancy and/or a substantial brain reorganization, possibly to accommodate a multi-faceted repertoire of complex behaviors associated with being a mother.